Hubungan Lama Penggunaan Gadget dengan Prestasi Belajar Siswa SDN Harapan Mulya Parongpong - Pebrina Manurung; Mori Agustina br Perangin-angin (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Prolonged use of gadgets can affect elementary school students' learning achievement. Objective: This study aims to determine the relationship between the length of gadget use and the learning achievement of class IV and V students at SDN Harapan Mulya Parongpong. Method: This research uses a quantitative correlation design with the Spearman rho statistical test. The questionnaire used to assess the length of gadget use consists of 7 questions. To assess student learning achievement, it is seen from the final semester grades. This research was conducted on class IV and V students of SDN Harapan Mulya Parongpong, totaling 58 respondents. The sampling method used was total sumpling. Results: Based on the results of data analysis, it is known that 72.4% of respondents used gadgets in the short category and the remaining 27.6% used gadgets in the long category. Based on statistical tests using the Spearman rho test, the p value = 0.307 > a value (0.05). Conclusion: The conclusion is that there is no relationship between the length of gadget use and the learning achievement of class IV and V students at SDN Harapan Mulya Parongpong. The suggestion given is that future researchers can look for other factors that can influence learning achievement.